Necrotizing Soft Tissue Infection Occurring after Exposure to Mycobacterium marinum - Shivani S. Patel; M. Lance Tavana; M. Sean Boger; Soe Soe Win; Bassam H. Rimawi (Case Reports in Infectious Diseases)
Cutaneous infections caused by Mycobacterium marinum have been attributed to aquarium or fish exposure after a break in the skin barrier. In most instances, the upper limbs and fingers account for a majority of the infection sites. While previous cases of necrotizing soft tissue infections related to M. marinum have been documented, the importance of our presenting case is to illustrate the aggressive nature of M. marinum resulting in a persistent necrotizing soft tissue infection of a finger that required multiple aggressive wound debridements, followed by an amputation of the affected extremity, in order to hasten recovery.